Immunogenic hotspots in the spacer domain of ADAMTS13 in immune‐mediated thrombotic thrombocytopenic purpura. (31st December 2020) - Velásquez Pereira, Leydi Carolina; Roose, Elien; Graça, Nuno A. G.; Sinkovits, György; Kangro, Kadri; Joly, Bérangère S.; Tellier, Edwige; Kaplanski, Gilles; Falter, Tanja; Von Auer, Charis; Rossmann, Heidi; Feys, Hendrik B.; et al.
Abstract: Background: Immune‐mediated thrombotic thrombocytopenic purpura (iTTP) is caused by anti‐ADAMTS13 autoantibodies inducing a severe deficiency of ADAMTS13. Epitope mapping studies on samples obtained during acute iTTP episodes have shown that the iTTP immune response is polyclonal, with almost all patients having autoantibodies targeting the spacer domain of ADAMTS13. Objectives: To identify the immunogenic hotspots in the spacer domain of ADAMTS13. Patients/methods: A library of 11 full‐length ADAMTS13 spacer hybrids was created in which amino acid regions of the spacer domain of ADAMTS13 were exchanged by the corresponding region of the spacer domain of ADAMTS1. Next, the full‐length ADAMTS13 spacer hybrids were used in enzyme‐linked immunosorbent assay to epitope map anti‐spacer autoantibodies in 138 samples from acute and remission iTTP patients. Results: Sixteen different anti‐spacer autoantibody profiles were identified with a similar distribution in acute and remission patients. There was no association between the anti‐spacer autoantibody profiles and disease severity. Almost all iTTP samples contained anti‐spacer autoantibodies against the following three regions: amino acid residues 588‐592, 602‐610, and 657‐666 (hybrids E, G, and M). Between 31% and 57% of the samples had anti‐spacer autoantibodies against amino acid regions 572‐579, 629‐638, 667‐676 (hybrids C, J, and N). In contrast, none of the samples had anti‐spacer autoantibodies against amino acid regions 556‐563, 564‐571, 649‐656, and 677‐685 (hybrids A, B, L, and O). Conclusion: We identified three hotspot regions (amino acid regions 588‐592, 602‐610, and 657‐666) in the spacer domain of ADAMTS13 that are targeted by anti‐spacer autoantibodies found in a large cohort of iTTP patients.